Modified vector coding analysis of trunk and lower extremity kinematics during maximum and sub-maximum back squats - Maddox, E. U.; Sievert, Z. A.; Bennett, H. J. (Journal of Biomechanics, 2020)
The back squat is a complex movement with significant demands on the lower extremities and trunk to raise an external load. The back squat is simultaneously an open and closed kinetic chain movement that requires coordination of the entire body for successful completion of the lift. Therefore, this study aimed to examine coordination of the thigh and shank, trunk and thigh, and the hip and knee during the concentric phase of maximum, supra-maximum (at 105% max), and sub-maximum (at 80% max) back squats. Fourteen resistance trained adults participated in this study. Maximum back squat loads were determined using a previously determined progressive load protocol. Motion capture of the trunk and lower extremities and ground reaction force data were recorded during all squats. Angle-angle plots and modified vector coding were performed to analyze segment and joint coupling angles and knee-hip moments. Overall, the concentric phase of back squats depict a transition from early knee dominance to hip dominance as the system ascends. Interestingly, all squats presented with coupling of thigh-rising and trunk-falling. Based on the angle-angle plots and the modified vector coding results, the prolonged coupling of trunk falling and thigh rising likely resulted in too large of a moment arm for the external load for the participants to overcome during Supramax conditions.